Clinical Legal Education in the Legal Aid Institution - Maria Ulfah (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical legal education in a Faculty of Law can be done through the curriculum or ongoing regular activities outside the curriculum. Many campuses have implemented clinical legal education in the compulsory courses or elective courses. It would be good if the clinical legal education has been implemented in the course of one eye, but the setting of clinical legal education in a college course for which has not been set is not easy to do. Difficulty setting of clinical legal education in the subjects did not dampen interest in developing clinical legal education on the campus. Faculty of Law, Universitas Katolik Parahyangan (UNPAR) develop it through ongoing routine activities included in the "Pengayoman" Legal Aid Institution (Pengayoman). Various activities in Pengayoman intended to achieve community service in the field of law committed by the students and faculty for approximately. This paper intended to deliver an analysis of activities organized by Pengayoman with clinical legal education that stems from the United States, known in Asia, and growing in Indonesia. The analysis also endeavour to identify a variety of benefits and barriers to clinical legal education through outside the curriculum of the Law Faculty. This paper opens with input for clinical legal education more leverage and more innovative.